Women discontinue antihypertensive drug therapy more than men. Evidence from an Italian population-based study. Issue 1 (January 2020) - Rea, Federico; Mella, Marta; Monzio Compagnoni, Matteo; Cantarutti, Anna; Merlino, Luca; Mancia, Giuseppe; Corrao, Giovanni
Abstract : Objective: Several factors affect adherence to antihypertensive drug treatment, but whether these factors include a sex difference is unclear. Aim of the study was to compare persistence with antihypertensive drug therapy between men and women in a large cohort of patients. Methods: The 60 526 residents of the Italian Lombardy Region aged 40–80 years newly treated with antihypertensive drugs during 2010 were identified and followed for 1 year after the first prescription. Discontinuation of treatment was defined as lack of prescription renewal for at least 90 days. Log-binomial regression models were fitted to estimate the risk ratio of treatment discontinuation in relation to sex. Other than for the whole population, analyses were stratified according to age, comorbidity status and the initial antihypertensive treatment strategy. Results: Thirty-seven percent of the patients discontinued the drug treatment during follow-up. Compared with women, men had a 10% lower risk of discontinuation of drug treatment (95% confidence interval: 8–12). Persistence on antihypertensive treatment was better in men than in women, this being the case in both younger (40–64 years) and older patients (65–80 years), in patients starting treatment with any major antihypertensive drug and in patients who had a low comorbidity status. There was no evidence that men and women had a different risk of treatment discontinuation when their comorbidity status was worse, or initial antihypertensive treatment was based on drug combinations. Conclusion: Our data show that in a real-life setting, men are more persistent to antihypertensive drug therapy than women. Abstract : Supplemental Digital Content is available in the text